1993
DOI: 10.1111/j.1469-7610.1993.tb01785.x
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of the Child Behavior Checklist with Structured Interview‐based Psychiatric Diagnoses of ADHD Children with and without Comorbidity

Abstract: We evaluated the convergence of CBCL scales with the diagnosis of ADHD and comorbid disorders in 133 ADHD and 118 normal control boys, aged 6-17 years old. We evaluated the strength of association between each CBCL scale and structured-interview derived diagnoses with Total Predictive Value (TPV) and the odds-ratio (OR). Excellent convergence was found between the CBCL Attention Problems scale with the diagnosis of ADHD, between the Delinquent Behavior scale and the diagnosis of CD, and between the Anxiety/Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
124
0
4

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(144 citation statements)
references
References 31 publications
16
124
0
4
Order By: Relevance
“…Many studies have found an excellent correspondence between quantitative measures of ADHD (e.g. scales derived from the Child Behavior Checklist, the Conners Scales and the ADHD Rating Scale IV) and the categorical diagnosis (Edelbrock, 1986;Bird et al 1987;Biederman et al 1993Biederman et al , 1996Chen et al 1994;Boyle et al 1997;Hudziak, 1997). These studies suggest that children with ADHD are at one extreme of a quantitative dimension and that, on this quantitative dimension, there is no obvious bimodality that separates children with ADHD from other children.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found an excellent correspondence between quantitative measures of ADHD (e.g. scales derived from the Child Behavior Checklist, the Conners Scales and the ADHD Rating Scale IV) and the categorical diagnosis (Edelbrock, 1986;Bird et al 1987;Biederman et al 1993Biederman et al , 1996Chen et al 1994;Boyle et al 1997;Hudziak, 1997). These studies suggest that children with ADHD are at one extreme of a quantitative dimension and that, on this quantitative dimension, there is no obvious bimodality that separates children with ADHD from other children.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate reading overactive behavior at the age of 3 years is referred to with the abbreviation OA and attention problems at the older ages is referred to with AP. An association between a high score on the AP scale (a T-score of 67 is often applied as the borderline cut-off) and ADHD as assessed by the DSM is reported by numerous studies [Bird et al, 1988;Edelbrock and Costello, 1988;Steingard et al, 1992;Biederman et al, 1993;Chen et al, 1994;Hudziak et al, 2002, in review].…”
Section: Measurementioning
confidence: 99%
“…This meant the selection of about 15% of children from among the population with the highest intensity of hyperactivity-impulsivity and/or inattention symptoms. Cutoff of one standard deviation above the mean for results of other rating scales of ADHD symptoms was shown to have good predictive value of diagnosis of ADHD (Biederman et al, 1993;Geller et al, 2004). Thus, we assumed that using this cutoff we would identify children with both clinical and subclinical ADHD.…”
Section: Methods Participantsmentioning
confidence: 99%